(untitled) (Historia, 2021)
One wonders how many South Mricans are aware of the fact thatRussian blood has flowed in the veins of some of their Cape Coloureds fornearly one hundred and fifty years. "A few Russian names persist inSimonstown to this day", says Mr. D. H. Varley who has done someresearch on this matter. That is not surprising for a Russian soldier,captured by the French in 1814 and again captured by the English at theBattle of Waterloo, was later brought by them to the Cape. He settledthere, married a "black woman" and had six children by her. The meetingwith this man, grown old by 1853, is one of the minor incidents describedby the Russian writer Ivan Alexandrevich Goncharov (1812-1891) in thechapter At the Cape of Good Hope of his book Fregat Pallada (FrigatePallas) which was published in Russia in 1856.= A good, and evidently the only existing tra